The self esteem of the workers pf the Agrarian University of the Jungle - Loli Pineda, Alejandro (2012)
The present work attempts to examine the self-esteem of workers within a public university located within the interior of the country and its relationship with demographic and social variables in a sample of 33% of the total university population. The results indicate that, in general terms, the self-esteem of the workers is low, while in regards to demographic variables (sex, marital status, level of study and years of residence) significant differences in self-esteem were found to exist.